„Zakazuje się stosowania kar cielesnych”. I co dalej? Nowoczesne strategie eliminacji przemocy w wychowaniu - Ewa Jarosz (Problemy Wczesnej Edukacji)
The paper presents the evidence based practice approach to eliminate violence against children. Here, the official ban of all forms of violence is seen as a very effective and needed means. But on the other hand, the ban is seen as a first step, because other activities are needed to eliminate corporal punishment. Today actions often come from analyses of effective practice. The paper presents main foundations of the modern strategies to stop corporal punishment, coming from the analysis of one example of such an initiative – the international cooperation that aimed at finding out effective practice in several countries in Europe where the ban has been already introduced.